Organometallic polyphosphorus and -arsenic ligands as linkers between pre-assembled linear CuI fragments1. Issue 14 (18th February 2015) - Fleischmann, Martin; Dütsch, Luis; Moussa, Mehdi Elsayed; Schindler, Andrea; Balázs, Gábor; Lescop, Christophe; Scheer, Manfred
<x xml:space="preserve">Abstract</x> We present a simple route to multimetallic CuI building blocks and their interaction with organometallic polyphosphorus and -arsenic linkers affording in novel polynuclear complexes or one-dimensional coordination polymers.